Pengaruh Flash Sale terhadap Keputusan Pembelian Produk di Shopee (Studi Kasus Pada Mahasiswa Pengguna Shopee) - Alnesa Oktriyani (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study is to find the effect of flash sales on the purchasing decisions of Bandung students who use Shopee. The sample used in this research was 106 respondents. This research uses quantitative descriptive methods with data analysis methods in the form of descriptive, correlation, regression and normality tests. The data collection technique uses a Google form in the form of a questionnaire distributed via social media and face to face. The results of the research obtained information that flash sales have a positive and significant impact on purchasing decisions.